Neuromodulation and psychotherapy for the treatment of anxiety spectrum disorders in primary otoneurological conditions: a systematic review - Gonçalves, Carlos Henrique; Ozorio Neubauer, Marianita; Thees Bortolotti, Júlia; Andrade Rios, Mônica; Nunes, Katia (Journal of Physiotherapy in Mental Health, 2026)
Anxiety spectrum disorders in patients with primary otoneurological conditions have been explored for treatment using psychotherapy and non-invasive brain stimulation. However, fragmented evidence complicates the identification of effective and safe clinical protocols. Objective: This study aimed to summarize the evidence on the efficacy of non-invasive neuromodulation and psychotherapy in managing anxiety spectrum disorders linked to otoneurological conditions. Material and methods: A registered PRISMA-guided systematic review (PROSPERO: CRD420250654796) analyzed clinical studies from PubMed, LILACS, SciELO, APA, and PePsic. Studies evaluating non-invasive brain stimulation and/or psychotherapy for anxiety in otoneurological conditions were included, with no restrictions on publication year or language. Two independent researchers searched for articles using the Ryyan tool. A third researcher participated in the final decision on the inclusion of pre-selected studies. The Cochrane Risk of Bias 2 (Rob2) tool was used to analyze the methodological quality of the included studies. Data on the study population, characteristics of the interventions, and results with the respective effect sizes were extracted from the selected studies. Results: Of 821 screened studies, 11 met eligibility criteria: seven randomized clinical trials, three observational studies, and one case report. Six studies supported psychotherapy, particularly cognitive behavioral therapy (CBT), while five highlighted the efficacy and safety of non-invasive brain stimulation. Of these, one tested the efficacy and safety of intermittent Theta Burst Stimulation (iTBS), one of non-invasive vagus nerve stimulation (nVNS) and three evaluated transcranial Direct Current Stimulation (tDCS). However, methodological heterogeneity, small sample sizes, and varying study designs and outcomes limited the ability to make a meta-analysis and recommend these interventions as first-line treatments. Conclusion: Psychotherapy and non-invasive neuromodulation show promise as complementary approaches to vestibular rehabilitation for anxiety in otoneurological conditions. However, current evidence is insufficient for widespread clinical recommendation. Further high-quality, large-scale studies are needed to establish standardized protocols and confirm efficacy and safety.